The effects of synbiotics supplementation on reducing chemotherapy-induced side effects in women with breast cancer: a randomized placebo-controlled double-blind clinical trial - Yasaman Khazaei; Ali Basi; Maria Luz Fernandez; Hossein Foudazi; Rafat Bagherzadeh; Farzad Shidfar (BMC, 2023)
Abstract Background The prevalence of breast cancer and its mortality rate are increasing rapidly among women worldwide. On other hand, the courses of chemotherapy as the main treatment for these patients are too much exhaustive and annoying. This study was designed to evaluate the use of synbiotics (probiotics + prebiotics) supplementation as a safe and inexpensive adjuvant treatment in reducing common chemotherapy side effects in women with breast cancer. Methods The current study was conducted on 67 women with definitive diagnosis of breast cancer who were hospitalized to receive one-day chemotherapy sessions, and met the inclusion criteria. The patients were randomly allocated to the intervention or control group to receive synbiotics or placebo, respectively. They received oral consumption of synbiotics supplements twice a day for 8 weeks. The primary outcome was the changes in severity or experience of chemotherapy complication, analyzed by intention to treat (ITT). The instruments included 7 validated questionnaires which were used to assess chemotherapy complications in the initiation, 4 weeks and 8 weeks after intervention. Dietary intake was measured by 24-h dietary recall at the beginning, week 4 and week 8. Data were analyzed by SPSS software version 24. P-value < 0.05 was considered as statistically significant. Results 67 breast cancer patients participated in the study. 8 weeks after intervention and adjusting the confounders, the severity of chemotherapy complications including unnormal defecation (P = 0.005) and fatigue (P < 0/001) decreased significantly in the synbiotics group compared to the placebo group. Furthermore, nausea/vomiting (P = 0.015), and anorexia (P < 0.001) were decreased at the end of the study compared to the first visit, but it was not statistically significant compared to the placebo group. Conclusions Synbiotics supplementation during chemotherapy can potentially reduce the severity of fatigue and abnormal defecation. It can help reduce anorexia and nausea/vomiting. Trial Registration This study was registered in the Iranian Registry of Clinical Trials (IRCT) (registered code: IRCT20091114002709N56) (date of registration: 5/5/2021). Direct link to the trial page: https://www.irct.ir/trial/54559 .